2020
DOI: 10.1177/1756284820939420
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in the procedure time of hybrid endoscopic submucosal dissection for early gastric neoplasms: a multi-center retrospective propensity score-matched analysis

Abstract: Background: Endoscopic submucosal dissection (ESD) for early gastric neoplasms is still a technically difficult and time-consuming procedure. Hybrid ESD (H-ESD) involves circumferential incision with partial submucosal dissection combined with subsequent mucosal resection by snaring, wherein the newly developed device allows us to perform H-ESD using a single device. This study aimed to determine the clinical outcomes of H-ESD compared with conventional ESD (C-ESD) for early gastric neoplasms. Methods: In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…Although there were concerns about the curability of hybrid ESD for lesion that were 10-15 mm in size, hybrid ESD achieved 100% en bloc resection and 93.8% complete resection, which were similar to what was obtainable with conventional ESD. This result was consistent with that of previous clinical studies on hybrid ESD and the treatment of gastric lesions[ 12 , 20 ]. Circumferential mucosal incision, followed by partial mucosal dissection before snaring in a planned manner improves curability using hybrid ESD.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although there were concerns about the curability of hybrid ESD for lesion that were 10-15 mm in size, hybrid ESD achieved 100% en bloc resection and 93.8% complete resection, which were similar to what was obtainable with conventional ESD. This result was consistent with that of previous clinical studies on hybrid ESD and the treatment of gastric lesions[ 12 , 20 ]. Circumferential mucosal incision, followed by partial mucosal dissection before snaring in a planned manner improves curability using hybrid ESD.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, a recently developed single multifunctional device (SOUTEN; Kaneka Medics, Tokyo, Japan) has enabled us to conduct hybrid ESD at lower cost with a single device than with conventional ESD[ 10 , 11 ]. Recently, we conducted a retrospective study, and showed that hybrid ESD with SOUTEN has shorter total procedure time than conventional ESD in ER for gastric neoplasms, and this finding was consistent with those of other previously reported studies on colonic neoplasms[ 8 , 12 ]. However, the real superiority of hybrid ESD with SOUTEN over conventional ESD remains to be determined since the previously conducted clinical studies had a limitation that SOUTEN was used only in hybrid the ESD group and not in the conventional ESD group where other common endoscopic knives, such as Dual knife, Flush knife and Splash-M knife were used, due to the ethical issues.…”
Section: Introductionsupporting
confidence: 91%
“…The H-ESD procedure will be performed, as described in detail elsewhere, using a SOUTEN high-frequency surgical knife [12,19]. SOUTEN will be xed with the snare closed, and only the distal tip will be exposed.…”
Section: Endoscopic Proceduresmentioning
confidence: 99%
“…In this study, to test the superiority of H-ESD over C-ESD, the sample size was estimated based on the primary endpoint (the logarithmically converted procedure time for ESD). According to a previous report comparing the treatment outcomes of C-ESD and H-ESD, the logarithmically converted procedure time (minutes, mean ± standard deviation (SD)) for C-ESD and H-ESD was 1.578 ± 0.225 and 1.244 ± 0.228, respectively [12]. Considering these results, we hypothesized that H-ESD would provide a 0.2 (37%) reduction in procedure time and estimated the SD of 0.3 conservatively.…”
Section: Sample Size Estimationmentioning
confidence: 99%
See 1 more Smart Citation